О регистрации спонтанной электромагнитной эмиссии литосферы в протяженной соляной штольне - Захаров, И.Г.; Шуман, В.Н. (Геофизический журнал, 2014)
Наведено результати вимірювань імпульсного потоку електромагнітного випромінювання в діапазоні частот 2,5—50 кГц (на рівні 3 дБ) у прямолінійній горизонтальній частині штольні завдовжки 700 м, розміщеній на глибині 260 м і позбавленій техногенних збудників завад. Синхронно та однотипним приладом проведено регістрацію імпульсного потоку випромінювання в пункті спостереження, розміщеного на денній поверхні над штольнею. Виконано також несинхронні вимірювання імпульсного потоку вздовж профілю, розташованого на денній поверхні під гострим кутом до азимута штольні. Виділено компоненту спонтанної електромагнітної емісії літосферного походження, не спотворену збудниками атмосферно-іоносферно-магнітосферного походження. Подано порівняльний аналіз записів імпульсного потоку, одержаних на денній поверхні та в штольні, глибина якої перевищує товщину скіншару в діапазоні частот 2,5—50 кГц, та їх геолого-геофізичну інтерпретацію. Results of measurements of impulse current of electromagnetic emission within frequency range 2,5—50kHz (by 3 dB level) in rectilinear horizontal part of natural salt 700 m long adit situated at the depth of 260m and without any technical sources of noise have been presented. Registration of impulse current of emission at the site of observation located at the surface above the adit was being conducted synchronously and by the instrument of the same type. In addition non-synchronous measurements of impulse current along the profile situated on the surface under acute angle to the course of the adit have been carried out. The component of spontaneous electromagnetic emission of lithosphere origin has been distinguished in the frequency range under consideration without noise bar from the sources of atmosphere-ionosphere-magnetosphere origin. Comparative analysis of impulse current records obtained at the day surface and in the adit with the depth exceeding the thickness of the skin-layer within the frequency ranges 2,5—50 kHz has been given and their geological-geophysical interpretation has been proposed.